Tradisi Hajat Buruan di Kampung Cipanawa, Kabupaten Bandung Tahun 2015 - 2021 - Alika Syafitri; Mahrus As'ad; Muhammad Riza (UIN Sunan Gunung Djati Bandung, 2023)
AbstractThe Sundanese people are generally Muslim and are very respectful of what their ancestral traditions have carried out. because of that there is a custom in respecting the noble time every month is not forgotten as ancestral heritage. In Indonesia, especially in Bandung Regency, Alamendah Village, there are interesting cultural characteristics to be studied. The culture in question is the Hajat overtime Tradition which is carried out every month of Safar. A community leader there said that the Hajat Overtime Tradition is a hereditary culture which is commemorated as asking for protection from Balai and all disasters in the month of Safar. This research reveals that most of the people of Alamendah Village are Muslims who still maintain their ancestral traditions, so that the celebration of talak bala is celebrated every month of Safar. This article applies historical methods which include heuristics, criticism, interpretation, and historical writing. The aim is to highlight the existence of the Hajat Buruan Tradition in Kampung Cipanawa which is still being preserved. Given that there are still very few writers who raise this tradition as research material. Islam and Sundanese Tradition in the Hajat Overtime Tradition is a form of acculturation that still occurs in Alamendah Village between Islam and Sundanese traditions. Keywords: Tradition, Hajat Buruan. AbstrakSuku Bangsa Sunda umumnya beragama Islam dan tabiatnya sangat menghormati apa yang sudah dijalankan oleh tradisi leluhurnya. Oleh sebab itu adanya adat dalam menghormati waktu mulia setiap bulan tidak dilupakan sebagai warisan leluhur. Di Indonesia, khususnya di Kabupaten Bandung Desa Alamendah terdapat kekhasan budaya yang menarik untuk dikaji. Budaya yang dimaksud yaitu Tradisi Hajat lembur yang dilakukan setiap bulan Safar. Seorang tokoh masyarakat disana menuturkan bahwa Tradisi Hajat Lembur merupakan budaya turun-temurun yang diperingati sebagai meminta perlindungan dari Balai dan segala musibah dalam bulan Safar. Penelitian ini mengungkapkan bahwa sebagian besar masyarakat Desa Alamendah adalah umat Islam yang masih melestarikan tradisi Sunda leluhurnya, sehingga perayaan talak bala diperingati setiap bulan Safar. Artikel ini mengaplikasikan metode sejarah yang meliputi heuristik, kritik, interpretasi, dan penulisan sejarah.Adapun tujuannya yaitu guna mengangkat eksistensi Tradisi Hajat Buruan di Kampung Cipanawa yang masih dilestarikan. Mengingat masih sedikit penulis yang mengangkat Tradisi ini sebagai bahan penelitian. Islam dan Tradisi Sunda dalam Tradisi Hajat Lembur merupakan bentuk akulturasi yang masih terjadi di Desa Alamendah antara Islam dan tradisi Sunda. Kata kunci : Tradisi, Hajat Buruan.